2013
DOI: 10.1016/j.chembiol.2013.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Selective HDAC1/HDAC2 Inhibitors Induce Neuroblastoma Differentiation

Abstract: Summary While cytotoxic chemotherapy remains the hallmark of cancer treatment, intensive regimens fall short in many malignancies, including high-risk neuroblastoma. One alternative strategy is to therapeutically promote tumor differentiation. We created a gene expression signature to measure neuroblast maturation, adapted it to a high-throughput platform, and screened a diversity oriented synthesis-generated small-molecule library for differentiation inducers. We identified BRD8430, containing a nine-membered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
71
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 45 publications
8
71
0
Order By: Relevance
“…The synergy of GSK126 and panobinostat is strong across a broad concentration range in all 4 of the MYCN-amplified neuroblastoma cell lines tested ( Figure 10B and Supplemental Figure 6). Our laboratory has previously demonstrated that HDAC1/2 inhibition induces neuroblastoma differentiation (55). Moreover, HDAC2 scored as one of the top neuroblastoma-specific dependency genes in the genome-scale CRISPR-Cas9 screen.…”
Section: E and F) Doxycycline Did Not Affect The Level Of Ezh2 In mentioning
confidence: 99%
“…The synergy of GSK126 and panobinostat is strong across a broad concentration range in all 4 of the MYCN-amplified neuroblastoma cell lines tested ( Figure 10B and Supplemental Figure 6). Our laboratory has previously demonstrated that HDAC1/2 inhibition induces neuroblastoma differentiation (55). Moreover, HDAC2 scored as one of the top neuroblastoma-specific dependency genes in the genome-scale CRISPR-Cas9 screen.…”
Section: E and F) Doxycycline Did Not Affect The Level Of Ezh2 In mentioning
confidence: 99%
“…PIM-1 inhibitors are in development as antitumor agents, including the ADP-competitive inhibitor SGI-1776. Additional small molecules targeting MYCassociated transcriptional regulators such as HDAC1, HDAC2 (Peart et al 2005;Frumm et al 2013), TFIIH (Titov et al 2011), P53-MDM2 (Felsher et al 2000), and DOT1L (Daigle et al 2011) are referenced in Table 1.…”
Section: Inhibition Of Myc-dependent Transcriptional Signalingmentioning
confidence: 99%
“…HDAC inhibition was recently demonstrated to enhance neuroblastoma differentiation. 25 Our investigation provides further evidence to highlight the therapeutic potential of targeting epigenetic regulators to promote neuroblastoma differentiation. Overall, preclinical trials, including our own, have demonstrated the pleotropic effects of JQ1 on neuroblastoma apoptosis, growth arrest, and differentiation and provide guidance for therapeutic strategies for the use of BET inhibitors in the treatment of high-risk neuroblastoma.…”
Section: Discussionmentioning
confidence: 71%